Pengaruh Kualitas Produk dan Kepercayaan Merek Terhadap Loyalitas Merek Pada Sepatu Skechers - Sugianto, Devin Orlando; Megawati, Megawati (Universitas Multi Data Palembang, 2024)
The purpose of this research is to measure the influence of product quality and brand trust on brand loyalty to Skechers shoes in Palembang City. This research is quantitative research using the previous measurement scale. The population in this research is The population in this research is consumers who have bought Skechers shoes in Palembang City with the number of samples used in this research totaling 320 samples which will be distributed to respondents, namely people who have bought Skechers shoes in Palembang City. The data source used is primary data obtained from the results of distributing questionnaires to respondents and secondary data used is in the form of the profile, history and organizational structure of the Palembang Skechers Brand Shoe Store. The analysis used in this research is validity analysis and. The results of this research show that the variables Product Quality and Brand Trust have a significant effect, while the variables Product Quality and Brand Trust have a significant effect simultaneously on the dependent variable (Brand Loyalty) on Skechers shoes in Palembang City.